Dampak Pembangunan dan Pendapatan terhadap Kemiskinan dan Kesenjangan di Kota Medan - Muhammad Anwar; Hanif Abrar; Yogi Pandapotan Siregar; Ahmad Fauzi Al Munawar (STIKes Ibnu Sina Ajibarang, 2025)
Firms big and small that can weather the economic storm will be able to hire more people and put more people out of poverty. Lacking proper asset segregation, small and medium-sized firms in Medan's Kampung Baru, Maimun District, tend to skimp on accounting. Intuition and expertise continue to guide the decision-making process for the majority of these heavy traders. One goal of PKM in basic accounting courses for SMBs is to teach students how to perform accounting in a way that is both methodical and crucial for measuring revenue, expenses, and profits. to keep up with the company's progress. In the Medan Maimun District of Kampung Baru Village, there are three steps to carrying out community service: conducting interviews and field observations, training, and mentoring and monitoring. Increased work motivation is one possible outcome of this activity's success in expanding participants' understanding of basic accounting and bookkeeping principles and practices.